Diffusion Tensor Imaging in Patients With Essential Tremor - Shin, D.H.; Han, B.S.; Kim, H.S.; Lee, P.H. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: The traditional paradigm has regarded essential tremor (ET) as a benign disorder. However, recent clinical, neuroimaging, and neuropathologic studies suggest that ET may be a progressive neurologic disorder. Based on clinicopathologic findings that cerebellum and its outflow are the key structures in ET and degeneration of gray matter in cerebellum is followed by consequent wallerian degeneration of white matter (WM) fibers, the aim of the present study was to investigate changes in anisotropy in patients with ET.MATERIALS AND METHODS: Fractional anisotropy (FA) images were generated from DTI data acquired at 1.5T in 10 patients with ET compared with 8 control subjects by using statistical parametric mapping to make voxel-by-voxel comparisons.RESULTS: Compared with the control subjects, the patients with ET exhibited significantly reduced FA (Puncorrected < .005) in the anterolateral portion of the right pons and decreased FA in the bilateral cerebellum, left retrorubral area of the midbrain, and bilateral deep WM, including the orbitofrontal, lateral frontal, parietal, and temporal WM.CONCLUSION: This study demonstrates that structural changes in the WM are extensive in patients with ET, supporting the findings of previous functional neuroimaging and pathologic studies.